Health Service‐Related Determinants of Health‐Seeking Behavior during Malaria Fever in a High‐Risk Region of Nepal - Ashok Kumar Paudel; Muni Raj Chhetri; Prem Prasad Panta; Nibha Rani Pandey (Health Science Reports)
ABSTRACT Background and Aims Malaria continues to be a significant global health challenge, leading to preventable illnesses and loss of lives. This cross‐sectional descriptive study, employing a mixed‐method approach, aimed to investigate the health service‐related factors affecting health‐seeking behavior during episodes of malaria fever in a high‐risk region of Nepal. Methods Using a cross‐sectional descriptive design with a mixed‐method approach, the research focused on Kanchanpur district, selected from 20 high‐risk malaria districts of Nepal. Belauri Municipality within Kanchanpur, identified for its concentration of high and moderate‐risk wards, was the specific study area. A random selection process identified 387 households for a comprehensive survey. Face‐to‐face interviews with household heads were conducted after obtaining written informed consent and ethical approval from the Nepal Health Research Council. Data analysis, employing statistical measures such as percentages, frequency, mean, and the Chi‐square test, was performed using SPSS version 20. Results Means of reaching the public health facility (AOR = 8.324, 95% CI = 3.677–18.844, p < 0.001), time to reach public health facility (AOR = 0.234, 95% CI = 0.059–0.918, p = 0.017), regular availability of service providers (AOR = 0.155, 95% CI = 0.054–0.442, p < 0.001), most of the time availability of service provider (AOR = 0.115, 95% CI = 0.039–0.334, p < 0.001), opening hours of health facility (AOR = 0.301, 95% CI = 0.156–0.581, p < 0.001), and perceived quality of service (AOR = 0.256, 95% CI = 0.154–0.424, p < 0.001), having to pay for transportation (COR = 0.275, 95% CI = 0.164–0.461, p < 0.001), travel cost (COR = 0.744, 95% CI = 0.640–0.865, p < 0.001), were the significant factors in health‐seeking behavior during malaria fever. Conclusion Collectively, these findings provide a comprehensive understanding of the multifaceted nature of health‐seeking behavior in the context of malaria fever and emphasize the importance of addressing various factors to improve healthcare utilization. Subsidized transportation for the poor helps to overcome financial barriers, establish additional facilities or mobile clinics to reduce travel time, ensure healthcare workforce availability, extend health facility hours, patient‐centered initiatives to enhance service quality can increase the likelihood of people seeking care from modern health facilities in Nepal.